2003
DOI: 10.1046/j.1365-2222.2003.01608.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in interleukin‐12‐producing ability by monocytes and their relevance to allergic diseases

Abstract: IL-12 appeared to play different roles in the pathogenesis of allergic diseases between younger and older ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
(23 reference statements)
1
12
0
1
Order By: Relevance
“…Understanding the molecular pathway that drives Th2 polarization and in turn induces allergen-specific IgE production in individuals with AD is critical to the further development of therapeutic approaches for AD and potentially for atopic disease in general. Some previous studies have shown deficient Th1 pathways in circulating antigen-presenting cells/monocytes (IL-12) in AD, but others have shown opposing results (Itazawa et al, 2003;Piancatelli et al, 2008). We therefore set out to explore the immunological outcome of the same antigenic stimulus in the skin of individuals with AD versus non-atopic controls.…”
Section: Or (B) Ifn-g Production By Peripheral Blood Mononuclear Cellmentioning
confidence: 99%
“…Understanding the molecular pathway that drives Th2 polarization and in turn induces allergen-specific IgE production in individuals with AD is critical to the further development of therapeutic approaches for AD and potentially for atopic disease in general. Some previous studies have shown deficient Th1 pathways in circulating antigen-presenting cells/monocytes (IL-12) in AD, but others have shown opposing results (Itazawa et al, 2003;Piancatelli et al, 2008). We therefore set out to explore the immunological outcome of the same antigenic stimulus in the skin of individuals with AD versus non-atopic controls.…”
Section: Or (B) Ifn-g Production By Peripheral Blood Mononuclear Cellmentioning
confidence: 99%
“…Recently, it has become clear that the differentiation of naïve helper lymphocyte (Th0) into Th1 or Th2 effectors is determined or at least affected by the following factors: soluble factors [IL-12 versus IL-4, IL-12 versus prostaglandin E 2 ], the nature and strength of the T cell receptor-mediated signal, and the nature, strength and/or timing of the co-stimulatory signals endowed by antigen 0165 presenting cells. A reduced ability to produce IL-12, which is a key cytokine for the induction of Th1 responses, has been proposed to lead to aberrant Th2 development in these disease conditions [8]. These findings suggest that cigarette smoke contains substances that may alter the Th1/Th2 balance via down-regulation of IL-12.…”
Section: Introductionmentioning
confidence: 99%
“…First, DCs from atopic individuals and their immediate blood monocyte precursors produce less IL-12p70 compared with nonatopic controls [19,20]. Second, sensitization to inhaled aller-gens occurs predominantly before the age of 12, when the capacity to produce IL-12 is severely reduced compared with adults, potentially explaining the Th2 bias at a young age [21,22]. In children at risk for allergic diseases, low IL-12 production by circulating DCs in the neonatal period is associated with stronger Th2 responses to inhaled and food allergens [23].…”
Section: Introductionmentioning
confidence: 99%